Hardware implementation of neural network-based engine model using FPGA - Magdy Saady, Marina; Hassan Essai, Mohamed (Alexandria engineering journal, 2022)
This paper implements an artificial neural network (ANN)-based engine model using the Field Programmable Gate Array (FPGA). The developed (ANN)-based engine model will be used to estimate the engine gas emissions to mitigate the harmful effects of these emissions on human health. Getting reliable and robust FPGA-based ANNs implementations depends on the optimal choice of activation function that will provide minimal area occupation on FPGA. This study introduces, implements, and investigates FPGA-based ANN-based engine models using five different activation functions. These implemented engine models were described using MATLAB/Simulink and hardware description language coder and carried out by Spartan -3E-500.CP132 FPGA platform from Xilinx. The performance of the implemented engine models was investigated in terms of area-efficient implementation and the regression values (R) to build a robust ANN-based engine model.